2019
DOI: 10.24093/awej/call5.19
|View full text |Cite
|
Sign up to set email alerts
|

A Study of EFL Students' Attitudes, Motivation and Anxiety towards WhatsApp as a Language Learning Tool

Abstract: This study aimed to explore the impact of WhatsApp on enhancing Saudi EFL students' language skills and areas. It also investigated EFL students' attitudes, motivation, and anxiety towards learning English via WhatsApp. The sample comprised 55 male and female students studying English at the College of Arts, University of Bisha, Saudi Arabia. A closed-ended questionnaire was used to collect quantitative data from the sample. The results revealed that WhatsApp has a positive impact on learning English as a fore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 0 publications
2
13
0
1
Order By: Relevance
“…This study corroborates several findings on motivation from previous studies in the Saudi context (Ali, 2019;Mohammed, 2015;Alrabai, 2014;Al-Qahtani,2013) which stressed the importance of identifying learners' goals for learning English. On the contrary to the findings of Salem (2006) and Obeidat (2005), which revealed no significant gender differences in overall motivation, the findings of this study showed highly significant motivation differences between male and female Saudi students in favor of females.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study corroborates several findings on motivation from previous studies in the Saudi context (Ali, 2019;Mohammed, 2015;Alrabai, 2014;Al-Qahtani,2013) which stressed the importance of identifying learners' goals for learning English. On the contrary to the findings of Salem (2006) and Obeidat (2005), which revealed no significant gender differences in overall motivation, the findings of this study showed highly significant motivation differences between male and female Saudi students in favor of females.…”
Section: Discussionsupporting
confidence: 91%
“…They found that those who do support an integrative approach to language study are usually more highly motivated and overall more successful in language learning. However, now the importance of instrumental motivation is also stressed (Zulfikar et al 2019;Nduwimana ,2019;Ali et al, 2019;Sengkey, 2018;Loganathan et al, 2016). Instrumental orientation, in this research, is seen to be more important than integrative orientation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies have examined the role of technology in enhancing Saudi learners' L2 motivation. The findings of a study by Ali and Bin-Hady (2019) revealed that learning English through WhatsApp had a positive influence on students' attitudes, anxiety, and motivation.…”
Section: Research On L2 Motivationmentioning
confidence: 99%
“…Technology changed the learning situations altogether, and the Saudi EFL context is no exception. Many studies have examined the impact of technology on English language learning in the Saudi context in formal learning (Al Zumor, Al Refaai, Bader Eddin & Aziz Al-Rahman, 2013;Ali, 2017;Ali & Bin-Hady, 2019;Ja'ashan, 2015). Some other studies looked into formal digital learning of English vocabulary (FDLEV), e.g.…”
Section: Introductionmentioning
confidence: 99%